Listeria and autophagy escape: Involvement of InlK, an internalin-like protein - Dortet, Laurent (Landes Bioscience, 2012)
Autophagy is a cell-autonomous mechanism of innate immunity that protects the cytosol against bacterial infection. Invasive bacteria, including Listeria monocytogenes, have thus evolved strategies to counteract a process that limits their intracellular growth. ActA is a surface protein produced by L. monocytogenes to polymerize actin and mediate intra- and intercellular movements, which plays a critical role in autophagy escape. We have recently investigated the role of another L. monocytogenes surface protein, the internalin InlK, in the infection process. We showed that in the cytosol of infected cells, InlK interacts with the major vault protein (MVP), the main component of cytoplasmic ribonucleoprotein particles named vaults. Although MVP has been implicated in a variety of key cellular process, its role remains elusive. We demonstrated that L. monocytogenes is able, via InlK, to decorate its surface with MVP in order to escape autophagic recognition. Strikingly, this new strategy used by L. monocytogenes to avoid autophagy is independent of ActA, suggesting that InlK-MVP interactions and actin polymerization are two processes that favor the infection process in the same way. Understanding the role of MVP may provide new insights into bacterial infection and autophagy.